The influence of rewards and the organizational environment on employee retention - Dias, Á.; Barros, S.; Pereira, L.; Costa, R. L.; Gonçalves, R. (International Journal of Productivity and Quality Management, 2022)
The loss of a qualified employee reveals itself as loss, once the company has invested time and money in training, attribution of benefits, among others. Thus, understanding employee retention factors represents a key dimension in human resources management. However, the study of factors influencing employee retention still needs further consolidation, especially regarding the role of rewards and the organisational environment. Using survey data to test the hypothesis through PLS-SEM, the findings reveal that rewards are directly linked to the organisational commitment and employee retention. Organisational environment influences significantly and positively organisational justice and organisational commitment. Furthermore, organisational justice was found to have a positive influence on retention, and organisational commitment reveals a positive relationship with retention. The organisational commitment mediation effect was also identified in the relations between rewards and employee retention, and organisational environment on employee retention.